If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + x = 6n + 22 Reorder the terms: -3 + x = 22 + 6n Solving -3 + x = 22 + 6n Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 22 + 3 + 6n Combine like terms: -3 + 3 = 0 0 + x = 22 + 3 + 6n x = 22 + 3 + 6n Combine like terms: 22 + 3 = 25 x = 25 + 6n Simplifying x = 25 + 6n
| -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) | | -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= | | 3h=-18 | | 48-5x=18 | | 3+4x+5x=48 | | 8(x-9)=15 | | -3+-b=1 | | 2x-(24/x)-8=0 | | x+2y-3=xy | | 15x^2-27y^2=12 | | 4(3x+7)=10 | | 7y+4(y-5)=4(y+1)-2 | | -7r=14 | | 3(5x+9)=37+19 | | x^2-27y^2=12 |